International Integration as Factor of Increase in Competitiveness of the Organizations of Cinematography - E. Y. Kolobova (Евразийская интеграция: экономика, право, политика, 2019)
Integration processes in modern conditions of managing are considered as a key issue of increase in Russian film company's competitive ability at the international level. International integration allows film companies to attract additional foreign sources of financing, creates opportunities for the competition in the international market of film spectacular services, provides conditions for cooperation with the leading foreign studios and cinema companies, modernization of funding mechanisms for film projects, participation in the international film projects. Overcoming obstacles to active international cooperation of the Russian cinematographers promotes formation of film company's competitive advantages that are necessary for business on the international film market.